“Tell Me Who You Are and I’ll Tell You What You Are”: Postcolonial Theory and Representations and Perceptions of Ethnic Minority Groups. The Case of Mizrahim and Israeli Arabs on Israeli Television - Katz, Nissim (The Journal of communication inquiry, 2025)
This theoretical article shows the benefits of using postcolonial theory in research of presentations and perceptions of ethnic minority groups on television. It introduces postcolonial theory and applies it to two minority ethnic groups in Israel: The Mizrahim and Israeli Arabs, analyzing their representations on mainstream Israeli television shows. This article also offers using a psychological theory called “media boundary situation” in order to discover perceptions of ethnic minority groups based on research of Mizrahim and Israeli-Arabs. The article assesses how postcolonial theory can be used to attain a better understating the unique representations of an ethnic groups and to develop an understanding of the perceptions of them.